Comparison of diverse platelet activation markers as indicators for left atrial thrombus in atrial fibrillation. (2nd January 2018) - Tarnowski, Daniel; Poitz, David M.; Plichta, Lina; Heidrich, Felix M.; Wiedemann, Stephan; Ruf, Tobias; Mierke, Johannes; Löhn, Tobias; Jellinghaus, Stefanie; Strasser, Ruth H.; Ibrahim, Karim; Pfluecke, Christian
Abstract: Atrial fibrillation (AF) is well known for being a major risk factor of thromboembolic stroke. We could recently demonstrate an association of monocyte–platelet aggregates (MPAs) with the degree of thrombogenicity in patients with AF. This study investigated platelet activation markers, as potential biomarkers for the presence of left atrial (LA) thrombus in patients with AF. One hundred and eight patients with symptomatic AF underwent transesophageal echocardiography (TEE) before scheduled cardioversion or pulmonary vein isolation. In order to determine the content of MPAs by flow-cytometric quantification analyses, blood was drawn on the day of TEE. The soluble CD40 Ligand (sCD40L) and soluble P-selectin (sP-selectin) were obtained by Cytometric Bead Arrays (CBA). D-dimer levels were detected by quantitative immunological determination of fibrin degradation products. Clinical, laboratory, and echocardiographic standard parameters were obtained from all patients, including the determination of the flow in the left atrial appendage (LAA). Patients with detected LA thrombus ( n = 28) compared with patients without thrombus ( n = 80) showed an increased number of common risk factors, such as age, diabetes, heart failure, and coronary artery disease (CAD). The presence of LA thrombus was associated with significantly increased levels of MPAs (147 ± 12 vs. 304 ± 29 per µl; p < 0.00), sCD40L (106.3 ± 31.0 vs. 33.5 ± 2.1 pg/ml, p = 0.027), and D-dimer (0.13 ± 0.02 vs. 0.69 ± 0.21 mg FEU/l, p = 0.015). In contrast, sP-selectin showed no association with LA thrombus. A multivariate regression analysis showed that MPAs, sCD40L as well as D-dimers were independent indicators for the existence of LA thrombus. MPAs above 170 cells/µl indicated LA thrombus with a high sensitivity of 93% and a specificity of 73% (OR 62, 95% CI. 6.9–557.2, p < 0.001) in patients with AF, whereas the D-dimer lost their quality as independent indicator by using the conventional cut-off of 0.5 mg/l within the regression analysis. MPAs, as well as the D-dimer, correlated significantly negatively with the flow in the LAA measured during TEE. The content of MPAs, sCD40L, and D-dimer, but not sP-selectin showed an increased dependence on LA thrombus in patients with AF. In our study group, MPAs showed the best diagnostic test accuracy of the compared platelet markers. The different results of the examined platelet activation markers could be an indication of diverse mechanisms of LA thrombus in AF. Further studies should evaluate whether determination of MPAs in clinical routine may suffice to indicate the presence of LA thrombus in patients with AF.